In whose name? : a public law theory of international adjudication - Bogdandy, Armin von, 1960-; Venzke, Ingo (Oxford : Oxford University Press, 2014)
International courts and tribunals make decisions which shape international law. Yet what grants them the legitimacy to make these decisions in the first place? This book proposes a theory of international public law that argues that these international courts democratically derive their legitimacy from the people and citizens.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 3, 2014).
Keywords: Jurisdiction (International law); International courts